Survey of student interest in football on physical education learning - Muhammad Kevin; Iyakrus Iyakrus; Ahmad Richard Victorian (Sriwijaya Journal of Sport, 2023)
The overall objective of this study is to better understand the level of interest of students at SDN 3 in Palembang in football, as well as the specific factors that contribute to that level of interest. The students in question are fifth and sixth grade students at SDN 33 in Palembang, Indonesia; The sample size is sixty. This research is an example of descriptive quantitative survey research. Information is collected through surveys, interviews, and observations which are then documented. The data collected showed that student interest was relatively high, accounting for 69.1% of the sample. Some of the things that attract this attention include intrinsic motivation, external influences, attitudes towards teachers and learning, family support, school resources, and widespread media exposure. Researchers recommend a more in-depth study of students' attitudes about other aspects of classroom learning and more concerted efforts to maximize student interest in classroom learning.